Leading for equity in uncertain times : a regenerative process - Candelarie, Doris (Emerald points., 2023)
Leading for Equity in Uncertain Times outlines a regenerative process for educational leaders developed in response to the disruption and crises caused by the social happenings of the Covid-19 pandemic, the racial justice reckoning after the George Floyd murder, and the political polarization paralyzing the United States. Each of these significant occurrences has left a lasting impact on school leaders, their teachers, students, families, and school communities. Educational leaders and scholars are just beginning to unravel the effects of this social phenomena on themselves personally and professionally, and on those they lead, teach, and support. Inequities that existed before are now magnified and untenable. Using a classic grounded theory research approach, Candelarie explores the implementation of The Regenerative Process, and how educational leaders can use this process to identify needed actions to respond to crisis, disruption, and change within their schools and educational organizations. These actions will regenerate education to a better, higher, more worthy state that is equitable and socially just.